Wilson chiral perturbation theory for dynamical twisted mass fermions vs lattice data: a case study - Cichy, Krzysztof; Zafeiropoulos, Savvas (Computer physics communications, 2019)
We compute the low lying eigenvalues of the Hermitian Dirac operator in lattice QCD with Nf=2+1+1 twisted mass fermions. We discuss whether these eigenvalues are in the ϵ-regime or the p-regime of Wilson chiral perturbation theory (χPT) for twisted mass fermions. Reaching the deep ϵ-regime is practically unfeasible with presently typical simulation parameters, but still the few lowest eigenvalues of the employed ensemble evince some characteristic ϵ-regime features. With this conclusion in mind, we develop a fitting strategy to extract two low energy constants from analytical ϵ-regime predictions at a fixed index. Thus, we obtain results for the chiral condensate and the low energy constant W8. We also discuss how to improve both the theoretical calculation and the lattice computation.
Available online 8 December 2018
Gesehen am 06.08.2019